KEANEKARAGAMAN, KERAPATAN DAN PENUTUPAN JENIS LAMUN DI PANTAI KASTELA, TERNATE SELATAN, MALUKU UTARA - Rakma Fitria Larasati; Made Mahendra Jaya; Angkasa Putra; Anthon Anthonny Djari; Kharisma Sako; Anis Khairunnisa; Diklawati Jatayu; Sarifah Aini; Herianto Suriadin (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
Kastela coastal waters are one of the tourist attractions in the coastal area of ​​Ternate city where seagrass is found. Information related to diversity, density and, the diverse cover is still lacking and has not been supported by previous scientific research, especially in the area of ​​Kastela Beach. Therefore, this study was conducted to determine the diversity, density and, cover of seagrass species on the Kastela coast, South Ternate. Seagrass diversity in Kastela Beach includes 6 types of seagrass, namely: Halodule pinifolia, Halophila ovalis, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium and, Enhalus acoroides. Based on the Shannon-Wienner index, the diversity of seagrass on the beach is classified as moderate with a value of 1.42 (station 1), 1.46 (station 2), 1.29 (station 3). Seagrass species Thalassia hemprichii has the highest density among seagrass species found on Kastela Beach with a density value of 580.27 individuals/m². At station 1, 358.27 individuals/m². At station 2, and station 3 it was dominated by Halodule pinifolia species as many as 326.53 individuals/m². For total seagrass closure at each station, especially station 1 and station 2, it was classified as rich or healthy (>60 %), where the value of station 1 was 124.16%/m², and station 2 was 95.2%/ m². Station 3 is classified as less healthy or less rich with a value of 59.79%/m².